Anatomical landmarks for tibial nerve motor branches in the management of spastic equinovarus foot after stroke: An ultrasonographic study - Alessandro Picelli; Elena Chemello; Elisabetta Verzini; Federico Ferrari; Annalisa Brugnera; Marialuisa Gandolfi; Leopold Saltuari; Angela Modenese; Nicola Smania (Medical Journals Sweden, 2019)
Objective: To identify the anatomical landmarks of tibial motor nerve branches to the gastrocnemii, soleus and tibialis posterior muscles for selective motor nerve blocks in the management of spastic equinovarus foot. Design: Observational study. Patients: Twenty-five chronic stroke patients with spastic equinovarus foot. Methods: Motor nerve branches to the gastrocnemii, soleus and tibialis posterior muscles were tracked in the affected leg, using ultrasonography, and located in the space (vertical, horizontal and deep) according to the position of the fibular head (proximal/distal) and a virtual line from the middle of the popliteal fossa to the Achilles tendon insertion (medial/lateral). Results: Mean coordinates for the gastrocnemius medialis motor branch were: 1.5 cm (standard deviation (SD) 2.7) vertical (proximal), 1.7 cm (SD 1.3) horizontal (medial), 1.1 cm (SD 0.4) deep; for the gastrocnemius lateralis motor branch: 0.9 cm (SD 2.2) vertical (proximal), 1.8 cm (SD 1.7) horizontal (lateral), 1.0 cm (SD 0.3) deep; for the soleus motor branch: 1.4 cm (SD 1.1) vertical (distal), 1.6 cm (SD 0.7) horizontal (lateral), 2.8 cm (SD 0.7) deep; and for the tibialis posterior motor branch: 4.3 cm (SD 1.5) vertical (distal), 1.9 cm (SD 0.9) horizontal (lateral), 4.2 cm (SD 0.8) deep. Conclusion: These findings may help in the identification of tibial motor nerve branches to the gastrocnemii, soleus and tibialis posterior muscles for selective motor nerve blocks in the management of spastic equinovarus foot.